To evaluate the equation \( y = 5 + 3x - 7 - 2x \) for \( x = 2 \) and \( x = 5 \) without simplifying first, follow these steps:
Step 1: Plug in \( x = 2 \)
-
Substitute \( x = 2 \) into the equation: \[ y = 5 + 3(2) - 7 - 2(2) \]
-
Now evaluate it step-by-step:
- Calculate \( 3(2) = 6 \)
- Calculate \( 2(2) = 4 \)
Substitute these back into the equation: \[ y = 5 + 6 - 7 - 4 \]
-
Now perform the addition and subtraction:
- First, calculate \( 5 + 6 = 11 \)
- Then \( 11 - 7 = 4 \)
- Finally, \( 4 - 4 = 0 \)
So when \( x = 2 \), \( y = 0 \).
Step 2: Plug in \( x = 5 \)
-
Substitute \( x = 5 \) into the equation: \[ y = 5 + 3(5) - 7 - 2(5) \]
-
Evaluate it step-by-step:
- Calculate \( 3(5) = 15 \)
- Calculate \( 2(5) = 10 \)
Substitute these back into the equation: \[ y = 5 + 15 - 7 - 10 \]
-
Now perform the addition and subtraction:
- First, calculate \( 5 + 15 = 20 \)
- Then \( 20 - 7 = 13 \)
- Finally, \( 13 - 10 = 3 \)
So when \( x = 5 \), \( y = 3 \).
Summary of Results
- For \( x = 2 \), \( y = 0 \).
- For \( x = 5 \), \( y = 3 \).